An Exploration of the Impact of Initial Timing of Physical Therapy on Safety and Outcomes After Concussion in Adolescents - Lennon, Anne (J Neurol Phys Ther, 2018)
BACKGROUND AND PURPOSE: Physical therapy (PT) is a management strategy increasingly recognized to facilitate recovery after concussion. The purpose of this study was to investigate the safety and outcomes of multimodal impairment-based PT at varying time points after injury in youth diagnosed with concussion. METHODS: Data were extracted retrospectively from medical records for patients who received PT for concussion-related impairments. Patient records were categorized into three cohorts based on the timing of PT implementation: 0–20 days following injury (early intervention), 21–41 days following injury (middle intervention), and 42 or more days following injury (late intervention). The primary outcome measure was Post-Concussion Symptom Inventory (PCSI) score from the beginning to end of the PT episode of care. Additional outcome measures included: number of PT sessions, duration of PT episode of care (days), and occurrence of unplanned visits to a healthcare provider. RESULTS: A total of 120 patient records (mean age of 14.77 years) were analyzed. Thirty-three, 39, and 48 individuals were categorized into the early, middle, and late intervention cohorts, respectively. There were no significant differences between intervention cohorts with regard to symptom change on the PCSI from the beginning to end of the PT episode of care, unplanned healthcare visits, number of PT sessions, or duration of PT episode of care. DISCUSSION AND CONCLUSION: Early initiation of PT may be safe and tolerable. Future prospective studies are needed to explore the efficacy of PT services administered early following injury to help characterize an optimal care plan for youth following concussion. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1).